2018
DOI: 10.1093/gastro/goy017
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow-derived CXCR4-overexpressing MSCs display increased homing to intestine and ameliorate colitis-associated tumorigenesis in mice

Abstract: Background and Objective Increasing interest has developed in the therapeutic potential of bone marrow-derived mesenchymal stem cells (MSCs) for the treatment of inflammatory bowel disease (IBD) and IBD-induced cancer. However, whether MSCs have the ability to suppress or promote tumor development remains controversial. The stromal cell-derived factor 1 (SDF-1)/C-X-C chemokine receptor type 4 (CXCR4) axis is well known to play a critical role in the homing of MSCs. In this study, we aimed to evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 69 publications
0
42
0
Order By: Relevance
“…Likewise, in chronic kidney disease, there is low level homing and poor survival of transplanted marrow‐derived MSCs 126 . In mice, marrow‐derived CXCR4‐overexpressing MSCs homed to the intestine and improved colitis in inflammatory bowel disease states 127 . Some of this differential ability to home is target tissue‐dependent, but intrinsic MSC alterations can also explain this varied capacity.…”
Section: Msc Homingmentioning
confidence: 99%
“…Likewise, in chronic kidney disease, there is low level homing and poor survival of transplanted marrow‐derived MSCs 126 . In mice, marrow‐derived CXCR4‐overexpressing MSCs homed to the intestine and improved colitis in inflammatory bowel disease states 127 . Some of this differential ability to home is target tissue‐dependent, but intrinsic MSC alterations can also explain this varied capacity.…”
Section: Msc Homingmentioning
confidence: 99%
“…Later, using the same murine model of colitis, it was demonstrated that AMD3100 also enhanced epithelial barrier integrity (245). A recent report has suggested a role of CXCR4 in mesenchymal stem cells (MSCs) homing to the inflamed intestinal tissues (246). MSCs play an important role in tissue repair and regeneration but also have immunoregulatory properties that might contribute to reduce inflammation (247).…”
Section: Cxcl12/cxcr4/ackr3 In Autoimmune Diseasesmentioning
confidence: 99%
“…Analogously, Liu et al 61 enforced surface expression of CXCR4 by lentiviral gene transfer in BM-MSCs to protect against experimental colitis via promoting the homing of BM-MSCs to inflamed colon where these cells could reduce inflammatory responses and suppress signal transducer and activator of transcription 3 (STAT3) phosphorylation. In addition, Zheng et al 62 also found that azoxymethane (AOM) and DSS-induced colitis-associated tumorigenesis were significantly attenuated when CXCR4-upregulated BM-MSCs were administrated. Interestingly, Nan et al 63 used the same method to enhance the expression of CXCR4 and IL-35 in BM-MSCs simultaneously.…”
Section: Improves the Efficacy Of Mscsmentioning
confidence: 99%